Neutralization of Lipopolysaccharide by Heat Shock Protein in Pediococcus pentosaceus AK‐23. Issue 7 (6th June 2017) - Asami, Kyoko; Kondo, Ayaka; Suda, Yoshihito; Shimoyamada, Makoto; Kanauchi, Makoto
Abstract: About 1000 species of bacteria are present in the human intestine. Some Gram‐negative bacteria such as Escherichia coli or Salmonella spp. among intestinal bacteria have lipopolysaccharide (LPS), which might induce inflammation of human intestines. Actually, LPS, especially its lipid A constituent, is toxic. Small amounts of LPS in bacteria cause inflammation of mucosa and other tissues in humans. Such bacteria may be regulated by beneficial lactic acid bacteria to maintain human health. Many lactic acid bacteria show cancer prevention activity and anti‐inflammatory activity in intestines. Recently, Pediococcus pentosaceus AK‐23 was isolated from fermentative vegetable pickles for neutralization of LPS. For this study, a protein for LPS neutralization was purified partly from P. pentosaceus AK‐23. For this study, a protein for LPS neutralization was purified partly from P. pentosaceus AK‐23, by ultrafiltration using a 300 kDa membrane and a 100 kDa membrane after cell wall digestion by lysozyme. Gel running blue native electrophoresis revealed the existence of a 217 kDa protein. The band of the protein having the ability to bind LPS on the gel was analyzed for amino acid homology. As the result, it is revealed as part of a subunit of heat shock protein (HSP). Furthermore, it displayed LPS binding or hydrophobic motifs. The protein neutralized LPS to release fatty acid as myristic acid and glucose from polysaccharide. These findings suggest that HSP in P. pentosaceus AK‐23 neutralizes LPS to decompose it compising fatty acid and polysaccharide.